2022
DOI: 10.1038/s41598-022-11170-3
|View full text |Cite
|
Sign up to set email alerts
|

Effects of phosphorus-modified biochar as a soil amendment on the growth and quality of Pseudostellaria heterophylla

Abstract: Phosphorus (P) deficiency in agricultural soil is a worldwide concern. P modification of biochar, a common soil conditioner produced by pyrolysis of wastes and residues, can increase P availability and improve soil quality. This study aims to investigate the effects of P-modified biochar as a soil amendment on the growth and quality of a medicinal plant (Pseudostellaria heterophylla). P. heterophylla were grown for 4 months in lateritic soil amended with P-modified and unmodified biochar (peanut shell) at dosa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(10 citation statements)
references
References 66 publications
0
9
1
Order By: Relevance
“…Given the alterations in P availability and diversity of the microbial community, the soil pH fluctuations remain a point to emphasize. Previous studies have reported the soil pH increments as a result of biochar and inorganic P amendments [17]. However, in this study, the increments in soil pH with biochar and inorganic P amendments were, perhaps, due to the alkaline nature of the biochar or the occurrence of carboxylic functional groups, as well as its oxidation properties [18].…”
Section: Discussioncontrasting
confidence: 55%
See 1 more Smart Citation
“…Given the alterations in P availability and diversity of the microbial community, the soil pH fluctuations remain a point to emphasize. Previous studies have reported the soil pH increments as a result of biochar and inorganic P amendments [17]. However, in this study, the increments in soil pH with biochar and inorganic P amendments were, perhaps, due to the alkaline nature of the biochar or the occurrence of carboxylic functional groups, as well as its oxidation properties [18].…”
Section: Discussioncontrasting
confidence: 55%
“…Using a spectrophotometer with a 420 nm wavelength, the P concentration was determined. The modified Tabatabai and Bremner (1969) [16] method was used to evaluate the soil phosphatase enzyme activity [17]. Next, 0.1 g of fresh soil was weighed into a 50 mL conical flask, which was then filled with a solution of toluene, modified universal buffer (pH 6.5), and p-nitrophenyl phosphate (PNP).…”
Section: Determination Of Soil Ph Available P and Phosphatase Enzyme ...mentioning
confidence: 99%
“…A better effect of using enriched biochar with phosphorus on plant growth occurred for the longer duration of pot tests, e.g. : 21 days (Nardis et al 2021 ), 65 days (Gunes et al 2014 ), 120 days (Ng et al 2022 ), which suggests conducting longer pot tests in the future using biochar as a soil additive. There were statistically significant differences for measuring the weight of fresh plants, the length of the plants, chlorophyll, and the leaf surface area for different groups, when comparing in a column (marked in Table 8 ).…”
Section: Resultsmentioning
confidence: 97%
“…The surface structure of raw biochar was different from activated biochars containing higher irregularities with fewer pores due to the low carbonization temperature (350°C) (Fu et al, 2009). However, biochars became highly porous after carbonizing and activating with H 3 PO 4 (Ng et al, 2022), with significantly increased surface area. The SEM images of activated biochars revealed the presence of tunnel‐shaped cracks and cylindrical pores, which acted as diffusion paths for MO molecules (Jjagwe et al, 2021), resulting in the higher sorption of MO compared to raw biochar.…”
Section: Resultsmentioning
confidence: 99%